PROGRAM POSYANDU KELILING DALAM UPAYA PEMENUHAN HAK IBU HAMIL DAN BALITA DI MASA PANDEMI COVID-19 - Astarina Arif (LPPM STAI Darul Falah, 2022)
Covid-19 is a global disease outbreak, so with this outbreak the entire community is negatively affected, one of which is the temporary suspension of posyandu. As a result of this temporary suspension of posyadu, pregnant women and toddlers do not get their rights as they should. With the STAI Darul Falah KKN Mandiri program in collaboration with posyandu cadres who initiated a program with the local area, especially Cimareme Village, which has an agenda for mobile posyandu, it is hoped that it will fulfill the rights of pregnant women and toddlers. The method used in this activity is in the form of education to the community in the form of direct counseling about the importance of implementing posyadu, preventing covid and things that must be considered when implementing mobile posyandu. The results of this activity are helping the community both in terms of fulfilling nutrition, providing adequate vitamins for pregnant women and toddlers can also help prevent the spread of COVID-19 by not crowding, always wearing masks and consuming nutritious food. Keyword: Posyandu Around, Covid-19, Mother and Toddler